Pendapatan Nelayan Kelong Apung Ikan Teri (Stolephorus Sp.) di Desa Selayar Kabupaten Lingga - Alfariz, Alfariz; Hafsar, Khairul; Tetty, Tetty (Department of Socio-economic Fisheries, Marine Science and Fisheries Faculty, Universitas Maritim Raja Ali Haji, 2021)
Selayar Village is a coastal area with the majority of the population as fishermen who use anchovy kelong (Stolephorus sp.)The method used in this research is a survey method, with a total of 15 respondents who own kelong anchovy (Stolephorus sp.). The research was carried out for 2 months starting from April-May 2021 in Selayar Village, Lingga Regency. Data analysis uses cost, revenue, and income analysis. Based on the results of the analysis, the total annual average income of the anchovy kelong business in Selayar Village is Rp245.700.000. The total average cost per year is Rp21.822.322. The average wage for managers and laborers of anchovy kelong per year is Rp134.326.607. The average net income per year for the owner of the anchovy kelong is Rp89.551.071.